DESIGN OF A WEB-BASED TOEFL SIMULATION APPLICATION - Yusril Maulana; Ai Rosita (Jurnal Darma Agung, 2022)
Currently, technological advancements have touched many aspects of life, one of which is the proliferation of various applications on cell phones, particularly those related to education or commonly referred to as web-based applications. Test Of English Foreign Language (TOEFL) is a measure of a person's ability to speak English. However, taking the TOEFL test is not cheap for one test, so preparation is needed mature to get the score as desired and save the cost of the test because it does not need to repeat. For that, we need a means application that can make it easier for someone in doing exercises or TOEFL Simulations Web-Based, with this application you can measure the ability of somebody in English.